Energy Saving Projects as Energy Security Factors - Kvon, Gulnara M.; Prokopyev, Alexey I.; Shestak, Victor A.; Ivanova, Svetlana A.; Vodenko, Konstantin V. (International Journal of Energy Economics and Policy, 2018)
National economic development, its effectiveness and competitiveness in domestic and foreign markets are directly determined by the country's economic resilience, which is able to ensure protection of its interests at the international level, promote economic growth and address public needs. One of the most important components of the country's national security is its energy security. In this regard, implementation of energy resource-saving technologies and enhancement of energy efficiency is of prime importance; in particular, solving heat related problems, i.e. heat transfer challenges while reforming and reorganizing Russian regional heat supply system. The main purpose of the paper is to study the issues connected with development and implementation of investment projects in the sphere of heat conservation and efficiency as one of the essential components contributing to energy efficiency programs in cities, regions, country. The survey methodology includes a quantitative method used to assess the effectiveness of an investment project which is based on the concept of discounting, the grouping technique, and tabular and graphical methods of data visualization. The paper presents result of evaluating the effectiveness of an investment project aimed at energy-saving, and energy efficient technologies in the field of heat saving. The projects implemented contribute to improvement and further development of the energy infrastructure of social-and-economic assets in order to improve their energy efficiency. The authors draw conclusions on the projects' effectiveness and urgency. Paper materials are of practical value for professionals involved in the study of investment projects in the field of energy and heat saving in order to ensure energy security of the country. Keywords: economy, economic security, energy security, energy efficiency, heat saving, investment project. JEL Classifications: D24; Q43; M31 DOI: https://doi.org/10.32479/ijeep.7143